DEVELOPING OF INTERACTIVE MATHEMATICS LEARNING MEDIA BASED MACROMEDIA FLASH 8 ON THE SUBJECT OF POLYHEDRON OF CLASS VIII SMP - Retno Rohmayati; Abdul Taram (Universitas Ahmad Dahlan, 2018)
Mathematics is a basic science that is very important and beneficial to the development of science and technology. The use of learning media based on technology becomes a tool alternative for teachers in presenting the subject of mathematics. The polyhedron subjects still considered difficult for some students. Learning media based on Macromedia Flash Profesional 8 is expected to be facilities that support learning. This research is a development that aims to produce instructional media using Macromedia Flash Profesional 8 in learning mathematics on the subject of polyhedron of class VIII SMP. This development study using the ADDIE development model that is Analysis, Design, Development, Implementation, Evaluation. Subjects were matter experts, media experts, and junior high school students of Muhammadiyah 2 Godean and Muhammadiyah 1 Gamping. The instrument used in this study is a questionnaire. The data analysis technique conducted qualitatively and quantitatively to calculate the results of the feasibility test score developed in instructional media. Based on the quality of every aspect of learning media, results of research-based math learning media development of mathematics learning media based onÂ Macromedia Flash 8 is from materials experts with excellent category, an average score is 96,67 from media experts with excellent category, an average score is 90, and the response of students with excellent category with an average score of 87,09. Based on the assessments, then the media-based mathematics learning Macromedia Flash 8 is very feasible to use in learning.